2021
DOI: 10.3389/fonc.2021.769163
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics and Transcriptomics Analysis on Metabolic Characteristics of Oral Lichen Planus

Abstract: ObjectiveTo explore metabolic biomarkers related to erosive and reticulated oral lichen planus (OLP) by non-targeted metabolomics methods and correlate metabolites with gene expression, and to investigate the pathological network pathways of OLP from the perspective of metabolism.MethodsA total of 153 individuals were enrolled in this study, including 50 patients with erosive oral lichen planus (EOLP), 51 patients with reticulated oral lichen planus (ROLP), and 52 healthy controls (HC). The ultra-high-performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Most of the differentially expressed metabolites identified in the serum sample were subgrouped as lipids and lipid-like molecules ( Yang et al, 2017 ). Another study showed that the content of glutamic acid decreased in the OLP patients, leading to OLP ( Xin et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the differentially expressed metabolites identified in the serum sample were subgrouped as lipids and lipid-like molecules ( Yang et al, 2017 ). Another study showed that the content of glutamic acid decreased in the OLP patients, leading to OLP ( Xin et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Second, there are neurotransmitter modulation factors, and studies have shown that schizophrenia is usually associated with neurotransmitter disorders, especially dopamine and acetylcholine ( 56 , 57 ). Whereas the development of LP is similarly associated with neurotransmitter disorders, we hypothesized that neurotransmitter abnormalities in patients with schizophrenia might reduce the risk of developing LP ( 58 ). In summary, mental factors have a close relationship with the occurrence and development of LP, and stress, emotional disorders, and personality traits play an important role in the pathogenesis of LP.…”
Section: Discussionmentioning
confidence: 99%
“…Results indicated that quercetin interfered with T helper cells (TH1/TH2) through the protein expression levels of cytokines (IL-6 and IFN-γ) to modulate immune response in OLP. Other recent studies have relied on bioinformatics-based approaches to gain biological insights contributing to understanding the molecular mechanism of LP [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%